Berlín 1961: Kennedy, Jrushchov y el lugar más peligroso del mundo - Kempe, Fredrick, 1954- (Serie Ensayo (Galaxia Gutenberg (Firm))., 2012)
Based on a new documents and interviews, this work is a look at the Berlin Crisis of 1961, with powerful applications for the present. In June 1961, Nikita Khrushchev called it "the most dangerous place on earth." He knew what he was talking about. Much has been written about the Cuban Missile Crisis a year later, but the Berlin Crisis of 1961 was more decisive in shaping the Cold War, and more perilous. For the first time in history, American and Soviet fighting men and tanks stood arrayed against each other, only yards apart. One mistake, one overzealous commander, and the trip wire would be sprung for a war that would go nuclear in a heartbeat. On one side was a young, untested U.S. president still reeling from the Bay of Pigs disaster. On the other, a Soviet premier hemmed in by the Chinese, the East Germans, and hard liners in his own government. Neither really understood the other, both tried cynically to manipulate events. And so, week by week, the dangers grew.